Waste Management Model in Gamalama Village Ternate City - Nini, Wa; Pobela, Elva (Universitas Lambung Mangkurat, 2024)
This research aims to identify waste management models and public perceptions about waste in Gamalama Village, Central Ternate City. This research used a qualitative descriptive. Data collection was carried out through interviews, questionnaires, documentation and testing the validity of the data using the triangulation method. The research results show that the volume of waste in Gamalama sub-district increased by 514,834 m3/day, and 187,914,319 m3/year. Waste management still uses the old model, namely picking up the source of the waste at the TPS and continuing it to the TPA. This risks of accumulation waste made people have a negative perception about waste management in Gamalama sub-district. Gamalama Village should implement the 3 R model (reuse, reduce and recycle) which can process waste into useful and economically valuable goods, and ultimately waste can be handled from upstream to downstream.